Analysis of Livestock Meat Production in Indonesia Using Fuzzy C-Means Clustering - Chalawatul Ais; Abdulloh Hamid; Dian Candra Rini Novitasari (Jurnal Ilmu Komputer dan Informasi, 2022)
The production of livestock in Indonesia is one type of food that the public can consume. Indonesia is still importing meat for food for its people. This study aims to classify provinces in Indonesia with high livestock meat production and low livestock meat production so that the government can maximize areas with high livestock meat production and can seek to increase livestock meat production in areas with low production. Clustering is needed to identify groups of livestock meat-producing provinces with high and low production. The data is grouped into 2 clusters using FCM with a silhouette index value of 0.95664, the first cluster with the highest meat production total in three provinces (West Java, Central Java, and East Java) and the second cluster with the lowest meat production total 31 provinces. West Java, Central Java, and East Java mostly work as livestock breeders due to the availability of sufficient land.